ANALISIS FAKTOR YANG MEMPENGARUHI DEPOSITO MUDHARABAH PADA BANK SYARIAH DI INDONESIA DAN MALAYSIA - Zulfa Nahdia Rahmi; Idah Zuhroh (Program Studi Ekonomi Pembangunan, 2020)
This research was conducted to determine how the development and determinant of Deposit Mudharabah Islamic Bank in Indonesia and Malaysia. The analysis technique used is the panel with a purposive sampling, data regression with quantitative inferential type of the research is using secondary data from the Financial Statement of data each Islamic bank in Indonesia and Malaysia and data from the World Bank in 2010-2018. Simultaneous testing results show that the value of 192.7748 F-count ≥ F-table 2.56 of the value can be inferred that the H0 is rejected, which means there are significant simultaneously and together in ROA, Profit Sharing, Inflation and GDP to variable Deposit Mudharabah Islamic Bank In Indonesia in 2010-2018. Further to the results of the F-count Malaysia 55.75571 ≥ F-table 2.56 of the value can be inferred that the H0 is rejected, which means there are significant simultaneously and together in ROA, Profit Sharing, Inflation and GDP to variable Deposit Mudharabah Islamic Bank In Malaysia in 2010-2018.